Conformity Testing Methods Of Intraoral Dental X-Ray Aircraft - Hajra, Hajra; ulandari, Rezki; Syam, Siti Surya; Jumardin, Jumardin; Zelviani, Sri; Agus, Jasdar; Harmini, Harmini (SAINFIS: Jurnal Sains Fisika, 2025)
Testing the suitability of intraoral dental X-ray devices has been carried out using the methods of collimation (conus) testing, voltage accuracy testing, irradiation time accuracy testing, reproducibility testing, and Half Value Layer (HVL) X-ray beam testing. The collimation test obtained the measurement result of the diameter or diagonal dimension parameter of the conus, which is 60 mm. The measured value of the X-ray beam dimension parameter is 57.26 mm and for the measured value of the focal point distance to the patient’s skin (SSD) parameter is 202 mm. The kVp accuracy test obtained error values at each kVp setting are 5.8%, 3.5%, and 3.5%. This error value is smaller than the test pass value so that the tube voltage accuracy test results are in accordance with the established standards. The irradiation time accuracy test found that the error values at each s-set were 2.0%, 1.2%, 0.9%, 0.8% and 0.8%. Reproducibility tests for radiation output (mGy) and tube voltage (kVp) obtained CV values are smaller than the predetermined test pass value of CV ≤ 0.05. X-ray beam quality testing (HVL) obtained measured HVL values at kVp are 2.28 mmAl, 2.31 mmAl and 2.47 mmAl which are greater than the test pass value.